Taxonomic revision of the Chinese Limnonectes (Anura, Dicroglossidae) with the description of a new species from China and Myanmar - Suwannapoom, Chatmongkon; Yuan, Zhi-Yong; Chen, Jin-Min; Hou, Mian; Zhao, Hai-Peng; Wang, Li-Jun; Nguyen, Truong Son; Nguyen, Truong Q.; Murphy, Robert W.; Sullivan, Jaqueline; Mcleod, David S.; Che, Jing (Zootaxa, 2016)
Phylogenetic reconstructions derived from DNA sequence data play a central role in documenting the number of species in a complex. Such analyses are pointing to the existence of many cryptic species, especially in poorly understood groups such as the genus Limnonectes, and the L. kuhlii species complex in particular. To understand the Limnonectes frogs of China, we reconstruct the major matrilineal genealogy of Limnonectes from China and Southeast Asia based on 12S rRNA, tRNAVal and 16S rRNA gene sequences. Based on new data we recognize five species of Limnonectes in China including L. bannaensis, L. fujianensis, L. fragilis, L. taylori (new record), and a new species from southern China and Myanmar. Phylogenetically, the new species is more closely related to the clade comprising L. taylori, L. megastomias, L. isanensis, L. nguyenorum, and L. jarujini from Thailand than to other Chinese species. This study supports previous findings of sympatric members of a species complex that are not each other’s closest relatives.